Living Islam in the Modern World: Examining Digital Da'wah in Indonesia from the Perspective of Fisher and Rinehart's Living Religions - Rahmat, Efendi; Truna, Dody S.; Hannah, Neng (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2025)
This study examines the phenomenon of digital da'wah in Indonesia using the theoretical framework of Fisher and Rinehart's Living Religions. The research applies a qualitative method through online observations and literature reviews. The findings reveal that digital da'wah has successfully created new spaces for the dissemination of Islam by adopting a more inclusive approach and adapting to technological advancements. Contrary to previous assumptions that Islam would lag behind modernity, this study demonstrates that Islamic preaching in the digital world enriches perspectives on religious teachings and enables Islamic messages to reach diverse audiences, particularly younger generations. However, this study also highlights the challenges that arise due to the lack of caution in delivering da'wah content, which can lead to controversy in the digital sphere. This research contributes to the development of a digital da'wah concept that responds to contemporary changes and emphasizes the importance of ethics in spreading religious messages online. Furthermore, it provides new insights into how Islamic da'wah can persist and evolve in the digital era without losing its core teachings